2016
DOI: 10.11604/pamj.2016.23.145.7546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water, sanitation and hygiene program outcomes shows knowledge-behavior gaps in Coast Province, Kenya

Abstract: IntroductionWater related diseases constitute a significant proportion of the burden of disease in Kenya. Water, sanitation and hygiene (WASH) programs are in operation nation-wide to address these challenges. This study evaluated the impact of the Sombeza Water and Sanitation Improvement Program (SWASIP) in Coast Province, Kenya.MethodsThis study is a cluster randomized, follow-up evaluation that compared baseline (2007) to follow-up (2013) indicators from 250 households. Twenty-five villages were selected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…For example, over two-thirds of the women in this study identified OD and/or use of bags and buckets (emptied into open drainages) as a primary cause of diarrhea and 70% said avoiding OD and/or use of bags and buckets was a key diarrhea prevention strategy; yet, close to 69% of the women reported that they rely on bags or buckets for urination/defecation at night and an additional 6% reported defecating in the open at night. One explanation for this findings might be, as evidence from other studies corroborates [ 42 , 43 ], that there is a knowledge-behavior gap when it comes to issues of WASH. Women may know, for example, that use of OD and/or bags and buckets is linked to poor health outcomes, but abandoning these practices may be hindered by additional more-pressing factors that prevent women, and their children and family members, from accessing clean water, safe sanitation, and or products for safe hygiene [ 17 , 44 ]. For example, several recent studies have provided evidence that women in sanitation-poor environments, e.g., informal settlements, often face a number of gender-specific barriers to access sanitation such as lack of privacy and dignity [ 18 , 45 , 46 ] and sexual violence and harassment associated with having to rely on community toilets or sites for OD at night or during menstruation [ 22 , 45 – 48 ].…”
Section: Discussionmentioning
confidence: 63%
“…For example, over two-thirds of the women in this study identified OD and/or use of bags and buckets (emptied into open drainages) as a primary cause of diarrhea and 70% said avoiding OD and/or use of bags and buckets was a key diarrhea prevention strategy; yet, close to 69% of the women reported that they rely on bags or buckets for urination/defecation at night and an additional 6% reported defecating in the open at night. One explanation for this findings might be, as evidence from other studies corroborates [ 42 , 43 ], that there is a knowledge-behavior gap when it comes to issues of WASH. Women may know, for example, that use of OD and/or bags and buckets is linked to poor health outcomes, but abandoning these practices may be hindered by additional more-pressing factors that prevent women, and their children and family members, from accessing clean water, safe sanitation, and or products for safe hygiene [ 17 , 44 ]. For example, several recent studies have provided evidence that women in sanitation-poor environments, e.g., informal settlements, often face a number of gender-specific barriers to access sanitation such as lack of privacy and dignity [ 18 , 45 , 46 ] and sexual violence and harassment associated with having to rely on community toilets or sites for OD at night or during menstruation [ 22 , 45 – 48 ].…”
Section: Discussionmentioning
confidence: 63%
“…The quasi-experimental study compared conventional CLTS in Ethiopia facilitated by Health Extension Workers (HEWs) to teacher-facilitated CLTS ( Crocker et al 2016b ). Of the two single-group evaluations, one was a baseline to end-line evaluation of the Philippines Phased Approach to Total Sanitation ( UNICEF 2016 ), and the other was a baseline to end-line evaluation of CLTS and other WaSH components in Kenya ( Schlegelmilch et al 2016 ). Finally, of the two comparative cross-sectional studies, one evaluated CLTS and Hygiene in Ethiopia to a control group ( BDS-Center for Development Research 2016 ), and the other assessed health outcomes in a CLTS group vs. a control group in Kenya ( Makotsi et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, such knowledge is not always translated into practice. For example, in some studies, participants who displayed good to high level of knowledge in regards to hygiene and sanitation failed to translate that set of knowledge into practice (Pang, Chua, & Hsu, 2015;Qadir, Akhtar, Khan et al, 2017;Schlegelmilch, Lakhani, Saunders, & Jhangri, 2016). Furthermore, a study showed that in spite of the parents and the children having the knowledge about hygiene, sanitation and helminthiasis, there is no action toward preventions (Masaku, Mwende, Odhiambo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%